NLRP3 Is Expressed in the Spiral Ganglion Neurons and Associated with Both Syndromic and Nonsyndromic Sensorineural Deafness - Penghui Chen; Longxia He; Xiuhong Pang; Xiaowen Wang; Tao Yang; Hao Wu (Neural Plasticity)
Nonsyndromic deafness is genetically heterogeneous but phenotypically similar among many cases. Though a variety of targeted next-generation sequencing (NGS) panels has been recently developed to facilitate genetic screening of nonsyndromic deafness, some syndromic deafness genes outside the panels may lead to clinical phenotypes similar to nonsyndromic deafness. In this study, we performed comprehensive genetic screening in a dominant family in which the proband was initially diagnosed with nonsyndromic deafness. No pathogenic mutation was identified by targeted NGS in 72 nonsyndromic and another 72 syndromic deafness genes. Whole exome sequencing, however, identified a p.E313K mutation in NLRP3, a gene reported to cause syndromic deafness Muckle-Wells Syndrome (MWS) but not included in any targeted NGS panels for deafness in previous reports. Follow-up clinical evaluation revealed only minor inflammatory symptoms in addition to deafness in six of the nine affected members, while the rest, three affected members, including the proband had no obvious MWS-related inflammatory symptoms. Immunostaining of the mouse cochlea showed a strong expression of NLRP3 in the spiral ganglion neurons. Our results suggested that NLRP3 may have specific function in the spiral ganglion neurons and can be associated with both syndromic and nonsyndromic sensorineural deafness.